A Consensual Qualitative Research Exploration of School Counselor Multicultural Education Behaviors. Issue 1 (January 2020) - Merlin-Knoblich, Clare; Moss, Lauren; Cholewa, Blaire; Springer, Sarah I.
In this consensual qualitative research study, we explored how school counselors enact multicultural education behaviors by studying the experiences of 10 practicing school counselors. We also examined barriers that prevent school counselors from implementing multicultural education. Participants described acknowledging their contexts, being influenced by intrapersonal factors and awareness of others, and implementing different types of interventions. We discuss implications for practicing school counselors to navigate barriers and enact multicultural education in their schools.